2019
DOI: 10.3390/ani10010069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slaughter Age on Muscle Characteristics and Meat Quality Traits of Da-Heng Meat Type Birds

Abstract: Due to the increasing demand for producing chickens with high meat quality, there is a need to determine its mode of action on chicken meat quality traits across a wider age spectrum. In this study, five groups of 200 male Da-Heng meat type birds were reared until slaughter age of 60, 90, 120, 150, 180 days old and breast muscle performance, meat quality traits, and myofiber characteristics were evaluated. The larger body weight and breast weight of chicken are based on larger myofiber diameter and area, less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 42 publications
5
38
2
2
Order By: Relevance
“…In addition, we found that the shear force increased with advancing age in both the breast muscle and leg muscle. The age-related findings in this study were consistent with those of L. Li and Uhlířová et al in chicken and geese [10,28]. Also, the shear force was positively correlated with the muscle fibers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, we found that the shear force increased with advancing age in both the breast muscle and leg muscle. The age-related findings in this study were consistent with those of L. Li and Uhlířová et al in chicken and geese [10,28]. Also, the shear force was positively correlated with the muscle fibers.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we investigated the muscle fiber characteristics of four muscular tissues in Yangzhou goose of different ages (1, 28, 70, 90 & 120 days). In general, the muscle fiber increased regularly with advancing age which was in agreement with the previous studies in birds and livestock [10,16]. In breast muscle, it stopped growth from 90 day thereafter.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, ostrich meat has a naturally higher postmortem pH than the 5.7-5.9 generally detected in meat, which results in better water-holding capacity, but shorter shelf life. With chicken, pH 24 significantly increases by bird age [36] but there are no data published on ostrich.…”
Section: Chemical Composition Of the Examined Meat Partsmentioning
confidence: 98%
“…As far as nutrition is concerned, poultry meat, particularly breast meat, quench the demand of the modern consumer for a high degree of unsaturation fatty acids and low fat, sodium, and cholesterol levels (Petracci and Cavani 2012). Nowadays, the importance of meat quality in the poultry industry could be validated by the enhanced sale of chicken meat as parts or further-processed products (Li et al 2019). Intramuscular fat (IMF) refers to the amount of lipids deposited within the muscle, including myometrium, myo brils, and endometrium.…”
Section: Introductionmentioning
confidence: 99%